Further motor unit studies in Duchenne muscular dystrophy. - McComas, A J (1977)
Numbers of functioning motor units have been estimated in 124 muscles of boys with Duchenne dystrophy; some of the patients were studied on several occasions. In the distal muscles examined (extensor digitorum brevis, thenar, and hypothenar muscles) the losses of units were probably present at birth and did not decrease with age. In contrast, the numbers of units and of excitable muscle fibres in the soleus muscles declined significantly, especially between the ages of 9 and 12 years.